Meningkatkan Kemampuan Kosakata Siswa dengan Menggunakan Flashcard pada Kelas 5A di SDN 23 Pangkalpinang Tahun Ajaran 2023-2024 - Feranty, Livia; Anggreini, Sonia; Meylani, Tasya; Darmawan, I Nyoman Pasek (JET (Journal of English Teaching), 2024)
Flashcard is viewed as one of the interesting and effective teaching media to teach English in general and vocabulary in particular. To enrich students’ vocabulary, flashcards can be used as a personal dictionary for students or as an instrument play a game applied as a strategy that facilitates active and fun learning. This study aims to solve problems students often face in learning English vocabulary and proves the effectiveness of using flashcards in increasing students’ vocabulary mastery. This study employed an action research design, in which flashcard was employed as the media of team game tournaments activities applied as the learning strategy of cooperative learning. This research involved 28 fifth graders at SDN 23 Pangkalpinang. The results show that flashcards use increased students’ vocabulary mastery. The mean score obtained by the students in the pre-test is 53.2. It increased to 79.1 in the post-test of the first cycle and to 85.7 in the post-test of the second cycle.